2018
DOI: 10.29140/jaltcall.v14n1.222
|View full text |Cite
|
Sign up to set email alerts
|

Significant predictors for effectiveness of blended learning In a language course

Abstract: A wide variety of technologies combined with traditional classroom methods can make learning easier in the digital age. This paper studied undergraduate students' learning performance and satisfaction after they had studied in a blended setting and investigated if variables of learner characteristics and course features would be predictors for effectiveness in a blended course. Data were gained from 149 students enrolled in a fundamental English course at a private university in Thailand, using a 5-rating scal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 21 publications
(30 reference statements)
1
19
0
1
Order By: Relevance
“…Understandably, effective implementation of BL methods has emerged as a key issue in subsequent information technology (IT) research (Kintu, Zhu, & Kagambe, 2017) that has aimed to describe successful blended learning environments mainly in terms of learner characteristics, design features and learning outcomes. Due to the limited research interest they have received within the CALL area (Wichadee, 2018),this study treats selfperceived digital literacy skills and satisfaction as key determinants for L2 learners' effective participation in the online module of the BL language course and investigates these in relation to the constructs of computer anxiety and self-efficacy.…”
Section: Digital Literacy and Satisfaction As Predictors Of Successful Blended Learningmentioning
confidence: 99%
“…Understandably, effective implementation of BL methods has emerged as a key issue in subsequent information technology (IT) research (Kintu, Zhu, & Kagambe, 2017) that has aimed to describe successful blended learning environments mainly in terms of learner characteristics, design features and learning outcomes. Due to the limited research interest they have received within the CALL area (Wichadee, 2018),this study treats selfperceived digital literacy skills and satisfaction as key determinants for L2 learners' effective participation in the online module of the BL language course and investigates these in relation to the constructs of computer anxiety and self-efficacy.…”
Section: Digital Literacy and Satisfaction As Predictors Of Successful Blended Learningmentioning
confidence: 99%
“…In this way, blended learning can be conceptualized as a design approach, whereby both face-to-face and online learning are made better by the presence of each other. Past research has shown that students have positive attitudes toward blended learning as a result of having more freedom and responsibility in learning, as well as convenience (Wichadee, 2018).…”
mentioning
confidence: 99%
“…Beberapa penelitian sebelumnya menunjukkan bahwa pembelajaran daring tidak selalu lebih mudah dan lebih menantang daripada pembelajaran konvensional (Cleveland-Innes & Campbell, 2012;Hava, 2021;Toro, 2019;Wichadee, 2018).…”
Section: Abstrakunclassified